2022
DOI: 10.3390/ph15080957
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol from Dietary Supplement to a Drug Candidate: An Assessment of Potential

Abstract: Resveratrol (RVT) is a well known phyto-chemical and is widely used in dietary supplements and botanical products. It shows a wide range of pharmacological/beneficial effects. Therefore, it can be a potential candidate to be developed as phyto-pharmaceutical. Multiple diseases are reported to be treated by the therapeutic effect of RVT since it has antioxidant, anti-cancer activity and anti-inflammatory activities. It also has a major role in diabetes, arthritis, cardiac disorder and platelet aggregation etc. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 120 publications
0
9
0
Order By: Relevance
“…Natural compounds from plants, fungi, and marine organisms have been widely used worldwide as dietary supplements or natural drugs in traditional medicine. These compounds show numerous beneficial effects, such as antioxidant, anti-inflammatory, and anti-cancer effects [ 3 , 14 , 92 , 93 , 94 , 95 , 96 ]. Phenethyl isothiocyanate (PEITC) is an isothiocyanate present in cruciferous vegetables that has shown antioxidant and anticancer activities [ 97 , 98 ].…”
Section: Role Of Metformin In Cotreatment With Sb203580 or Phenethyl ...mentioning
confidence: 99%
“…Natural compounds from plants, fungi, and marine organisms have been widely used worldwide as dietary supplements or natural drugs in traditional medicine. These compounds show numerous beneficial effects, such as antioxidant, anti-inflammatory, and anti-cancer effects [ 3 , 14 , 92 , 93 , 94 , 95 , 96 ]. Phenethyl isothiocyanate (PEITC) is an isothiocyanate present in cruciferous vegetables that has shown antioxidant and anticancer activities [ 97 , 98 ].…”
Section: Role Of Metformin In Cotreatment With Sb203580 or Phenethyl ...mentioning
confidence: 99%
“…In two food supplements the declared resveratrol contents were higher than 150 mg per unit (250 mg and 300 mg), however, the determined contents were lower than 150 mg per unit (144.9 mg and 147.3 mg) [ 16 ]. Surprisingly, a recently published list of products containing 20 to 1400 mg of resveratrol per serving included more than 45% of the products with the declared resveratrol contents higher than 150 mg/unit [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…Regarding OS markers, RV has been shown to exert antioxidant effects through two mechanisms: (i) through direct interaction with RL and ROS and (ii) through its ability to increase the activity of antioxidant enzymes [ 52 ]. In this sense, the first mechanism is due to the polyphenolic nature of RV, mainly the free hydroxyl group in position 4, since the extraction of its hydrogen allows electrons to be mobilized throughout the chemical structure of RV and gives it redox characteristics, which allow it to interact with FR and ROS, making it an excellent scavenger of hydroxyl, peroxide and superoxide [ 52 , 53 ]; as a consequence of this activity, it can minimize or prevent the oxidation of polyunsaturated fatty acids that are abundant in cell membranes, protecting them from oxidative damage [ 52 , 53 , 54 ]. In line with this, the results of two randomized double-blind clinical trials found a significant decrease in malondialdehyde (MDA) levels, a direct biomarker of lipid peroxidation in membranes, with doses of 200 and 500 mg/day of RV in subjects with T2D [ 33 , 55 ].…”
Section: Discussionmentioning
confidence: 99%